The Effect of Carbonization Time on The Quality Coconut Shell and Melinjo Shell Briquettes - Rintis Manfaati; Yusmardhany Yusuf; Heni Anggorowati; Alfiana Adhitasari (Universitas Negeri Semarang, 2025)
This study explores the impact of different durations of carbonization on the production of briquettes. Briquettes are produced through carbonization process conducted at different time intervals, including 30, 60, 90, 120, and 150 minutes, with a ratio composition of coconut shells and melinjo shells is 90:10. Various carbonization durations were examined to determine their influence on briquette properties, consisting of calorific value, water content, ash content, volatile matter, and density. The conclusion of this study reveals that a longer duration of carbonization results in higher values of calorific and ash content compared to shorter durations. Moreover, longer carbonization periods are associated with reductions in water content, volatile matter, and density of the briquettes. Through experimental analysis, the research indicates that the most effective duration of carbonization is 150 minutes. The briquettes produced with a 150-minute carbonization period possess a calorific value 6,004 cal/g, water content 4.65 %, ash content 4.78 %, volatile matter 6.17 %, and density 0.86 gr/cm3.